Nucleotide exchange factors Fes1 and HspBP1 mimic substrate to release misfolded proteins from Hsp70 - Gowda, Naveen K. C.; Kityk, Roman; Mayer, Matthias P. (Nature structural & molecular biology, 2018)
Protein quality control depends on the tight regulation of interactions between molecular chaperones and polypeptide substrates. Substrate release from the chaperone Hsp70 is triggered by nucleotide-exchange factors (NEFs) that control folding and degradation fates via poorly understood mechanisms. We found that the armadillo-type NEFs budding yeast Fes1 and its human homolog HspBP1 employ flexible N-terminal release domains (RDs) with substrate-mimicking properties to ensure the efficient release of persistent substrates from Hsp70. The RD contacts the substrate-binding domain of the chaperone, competes with peptide substrate for binding and is essential for proper function in yeast and mammalian cells. Thus, the armadillo domain engages Hsp70 to trigger nucleotide exchange, whereas the RD safeguards the release of substrates. Our findings provide fundamental mechanistic insight into the functional specialization of Hsp70 NEFs and have implications for the understanding of proteostasis-related disorders, including Marinesco–Sjögren syndrome.